PJMHS 2022
DOI: 10.53350/pjmhs22166828
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes: Insights into Thyroid Hormones

Abstract: Numerous physiological and pathological processes must be controlled for the thyroid gland to function properly. Research utilising both animal models and human subjects has demonstrated that thyroid hormones regulate cellular processes that are crucial for most age-related diseases. Furthermore, both hyperthyroidism and hypothyroidism have been associated to the onset of several kinds of diabetes, proving the intricacy of the molecular processes regulated by thyroid hormones. In this article, we provide a sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Thyroxine (T4) is not properly converted to triiodothyronine (T3) in peripheral tissues in T2DM, which also lowers the levels of thyroid-stimulating hormone (Kalra et al, 2021). Researchers have shown that carbohydrate metabolism and pancreatic functions are regulated by thyroid hormones (THs) (Shehzad et al, 2022). (T3) regulates cell activity physiologically by influencing how much glucose is taken in by pancreatic cells, which in turn regulates the release of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroxine (T4) is not properly converted to triiodothyronine (T3) in peripheral tissues in T2DM, which also lowers the levels of thyroid-stimulating hormone (Kalra et al, 2021). Researchers have shown that carbohydrate metabolism and pancreatic functions are regulated by thyroid hormones (THs) (Shehzad et al, 2022). (T3) regulates cell activity physiologically by influencing how much glucose is taken in by pancreatic cells, which in turn regulates the release of insulin.…”
Section: Introductionmentioning
confidence: 99%